Social media analytics: a tool for the success of online retail industry. (4th July 2019) - Ayodeji, Ogunmola Gabriel; Kumar, Vikas
Social media has become a part of life for a larger segment of the people globally. Businesses are also taking advantage of it, to instantly and easily create and share information with the customers and get benefited from this seamless communication. As a result of the increase in both social media platforms and users, the need to monitor, extract, analyse and report the data being created on these platforms has also increased for the Businesses. Present work identifies the social media analytics (SMA) process and online retail application; it identifies the different phases of the SMA process with their integration to the online retail strategy, challenges, and opportunities. SMA metrics for customer life-cycle (acquisition to enhancement) are discussed. A comparative analysis has been presented for different SMA tools to identify their utility to the online retail.